square_1.miz
begin
reserve a,b,c,x,y,z for
Real;
scheme ::
SQUARE_1:sch1
RealContinuity { P,Q[
object] } :
ex z st for x, y st P[x] & Q[y] holds x
<= z & z
<= y
provided
A1: for x, y st P[x] & Q[y] holds x
<= y;
set Y = { z where z be
Element of
REAL : Q[z] };
set X = { z where z be
Element of
REAL : P[z] };
A2: X
c=
REAL
proof
let x be
object;
assume x
in X;
then ex z be
Element of
REAL st z
= x & P[z];
hence thesis;
end;
Y
c=
REAL
proof
let x be
object;
assume x
in Y;
then ex z be
Element of
REAL st z
= x & Q[z];
hence thesis;
end;
then
reconsider X, Y as
Subset of
REAL by
A2;
for x,y be
Real st x
in X & y
in Y holds x
<= y
proof
let x,y be
Real;
assume that
A3: x
in X and
A4: y
in Y;
A5: ex z be
Element of
REAL st z
= y & Q[z] by
A4;
ex z be
Element of
REAL st z
= x & P[z] by
A3;
hence thesis by
A1,
A5;
end;
then
consider z be
Real such that
A6: for x,y be
Real st x
in X & y
in Y holds x
<= z & z
<= y by
AXIOMS: 1;
take z;
let x, y;
assume that
A7: P[x] and
A8: Q[y];
y is
Element of
REAL by
XREAL_0:def 1;
then
A9: y
in Y by
A8;
x is
Element of
REAL by
XREAL_0:def 1;
then x
in X by
A7;
hence thesis by
A6,
A9;
end;
theorem ::
SQUARE_1:1
((
min (x,y))
+ (
max (x,y)))
= (x
+ y)
proof
per cases ;
suppose
A1: x
<= y;
then (
min (x,y))
= x by
XXREAL_0:def 9;
hence thesis by
A1,
XXREAL_0:def 10;
end;
suppose
A2: x
> y;
then (
min (x,y))
= y by
XXREAL_0:def 9;
hence thesis by
A2,
XXREAL_0:def 10;
end;
end;
theorem ::
SQUARE_1:2
for x,y be
Real st
0
<= x &
0
<= y holds (
max (x,y))
<= (x
+ y)
proof
let x,y be
Real;
assume that
A1:
0
<= x and
A2:
0
<= y;
now
per cases by
XXREAL_0: 16;
suppose
A3: (
max (x,y))
= x;
(x
+
0 )
<= (x
+ y) by
A2,
XREAL_1: 7;
hence thesis by
A3;
end;
suppose
A4: (
max (x,y))
= y;
(y
+
0 )
<= (y
+ x) by
A1,
XREAL_1: 7;
hence thesis by
A4;
end;
end;
hence thesis;
end;
definition
let x be
Complex;
::
SQUARE_1:def1
func x
^2 ->
number equals (x
* x);
correctness ;
end
registration
let x be
Complex;
cluster (x
^2 ) ->
complex;
coherence ;
end
registration
let x be
Real;
cluster (x
^2 ) ->
real;
coherence ;
end
definition
let x be
Element of
COMPLEX ;
:: original:
^2
redefine
func x
^2 ->
Element of
COMPLEX ;
coherence by
XCMPLX_0:def 2;
end
theorem ::
SQUARE_1:3
for a be
Complex holds (a
^2 )
= ((
- a)
^2 );
theorem ::
SQUARE_1:4
for a,b be
Complex holds ((a
+ b)
^2 )
= (((a
^2 )
+ ((2
* a)
* b))
+ (b
^2 ));
theorem ::
SQUARE_1:5
for a,b be
Complex holds ((a
- b)
^2 )
= (((a
^2 )
- ((2
* a)
* b))
+ (b
^2 ));
theorem ::
SQUARE_1:6
for a be
Complex holds ((a
+ 1)
^2 )
= (((a
^2 )
+ (2
* a))
+ 1);
theorem ::
SQUARE_1:7
for a be
Complex holds ((a
- 1)
^2 )
= (((a
^2 )
- (2
* a))
+ 1);
theorem ::
SQUARE_1:8
for a,b be
Complex holds ((a
- b)
* (a
+ b))
= ((a
^2 )
- (b
^2 ));
theorem ::
SQUARE_1:9
for a,b be
Complex holds ((a
* b)
^2 )
= ((a
^2 )
* (b
^2 ));
theorem ::
SQUARE_1:10
Th10: for a,b be
Complex st ((a
^2 )
- (b
^2 ))
<>
0 holds (1
/ (a
+ b))
= ((a
- b)
/ ((a
^2 )
- (b
^2 )))
proof
let a,b be
Complex;
assume ((a
^2 )
- (b
^2 ))
<>
0 ;
then (a
- b)
<>
0 ;
hence (1
/ (a
+ b))
= ((1
* (a
- b))
/ ((a
+ b)
* (a
- b))) by
XCMPLX_1: 91
.= ((a
- b)
/ ((a
^2 )
- (b
^2 )));
end;
theorem ::
SQUARE_1:11
Th11: for a,b be
Complex st ((a
^2 )
- (b
^2 ))
<>
0 holds (1
/ (a
- b))
= ((a
+ b)
/ ((a
^2 )
- (b
^2 )))
proof
let a,b be
Complex;
assume ((a
^2 )
- (b
^2 ))
<>
0 ;
then ((a
+ b)
* (a
- b))
<>
0 ;
then (a
+ b)
<>
0 ;
hence (1
/ (a
- b))
= ((1
* (a
+ b))
/ ((a
- b)
* (a
+ b))) by
XCMPLX_1: 91
.= ((a
+ b)
/ ((a
^2 )
- (b
^2 )));
end;
theorem ::
SQUARE_1:12
0
<> a implies
0
< (a
^2 ) by
XREAL_1: 63;
theorem ::
SQUARE_1:13
Th13:
0
< a & a
< 1 implies (a
^2 )
< a
proof
assume that
A1:
0
< a and
A2: a
< 1;
(a
* a)
< (a
* 1) by
A1,
A2,
XREAL_1: 68;
hence thesis;
end;
theorem ::
SQUARE_1:14
Th14: 1
< a implies a
< (a
^2 )
proof
assume 1
< a;
then (a
* 1)
< (a
* a) by
XREAL_1: 68;
hence thesis;
end;
Lm1:
0
< a implies ex x st
0
< x & (x
^2 )
< a
proof
assume
A1:
0
< a;
per cases ;
suppose
A2: 1
<= a;
reconsider x = (2
" ) as
Real;
take x;
thus
0
< x;
thus thesis by
A2,
XXREAL_0: 2;
end;
suppose
A3: a
< 1;
take x = a;
thus
0
< x by
A1;
thus thesis by
A1,
A3,
Th13;
end;
end;
theorem ::
SQUARE_1:15
Th15:
0
<= x & x
<= y implies (x
^2 )
<= (y
^2 )
proof
assume that
A1:
0
<= x and
A2: x
<= y;
A3: (x
* y)
<= (y
* y) by
A1,
A2,
XREAL_1: 64;
(x
* x)
<= (x
* y) by
A1,
A2,
XREAL_1: 64;
hence thesis by
A3,
XXREAL_0: 2;
end;
theorem ::
SQUARE_1:16
Th16:
0
<= x & x
< y implies (x
^2 )
< (y
^2 )
proof
assume that
A1:
0
<= x and
A2: x
< y;
A3: (x
* y)
< (y
* y) by
A1,
A2,
XREAL_1: 68;
(x
* x)
<= (x
* y) by
A1,
A2,
XREAL_1: 64;
hence thesis by
A3,
XXREAL_0: 2;
end;
Lm2:
0
<= x &
0
<= y & (x
^2 )
= (y
^2 ) implies x
= y
proof
assume that
A1:
0
<= x and
A2:
0
<= y;
assume
A3: (x
^2 )
= (y
^2 );
then
A4: y
<= x by
A1,
Th16;
x
<= y by
A2,
A3,
Th16;
hence thesis by
A4,
XXREAL_0: 1;
end;
definition
let a be
Real;
assume
A1:
0
<= a;
::
SQUARE_1:def2
func
sqrt a ->
Real means
:
Def2:
0
<= it & (it
^2 )
= a;
existence
proof
defpred
Y[
Real] means
0
<= $1 & a
<= ($1
^2 );
defpred
X[
Real] means $1
<=
0 or ($1
^2 )
<= a;
a
<= (a
+ 1) by
XREAL_1: 29;
then
A2: (
0
+ a)
<= (((a
^2 )
+ a)
+ (a
+ 1)) by
A1,
XREAL_1: 7;
A3:
now
let x, y such that
A4:
X[x] and
A5:
Y[y];
per cases ;
suppose x
<=
0 ;
hence x
<= y by
A5;
end;
suppose not x
<=
0 ;
then (x
^2 )
<= (y
^2 ) by
A4,
A5,
XXREAL_0: 2;
hence x
<= y by
A5,
Th16;
end;
end;
consider z such that
A6: for x, y st
X[x] &
Y[y] holds x
<= z & z
<= y from
RealContinuity(
A3);
take z;
A7: ((a
+ 1)
^2 )
= (((a
^2 )
+ a)
+ (a
+ 1));
hence
0
<= z by
A1,
A2,
A6;
assume
A8: (z
^2 )
<> a;
now
per cases by
A8,
XXREAL_0: 1;
suppose
A9: z
<=
0 ;
then z
=
0 by
A1,
A7,
A2,
A6;
then ex c st
0
< c & (c
^2 )
< a by
A1,
A8,
Lm1;
hence contradiction by
A1,
A7,
A2,
A6,
A9;
end;
suppose
A10: (z
^2 )
< a & not z
<=
0 ;
set b = (a
- (z
^2 ));
A11:
0
< b by
A10,
XREAL_1: 50;
then
consider c such that
A12:
0
< c and
A13: (c
^2 )
< (b
/ 2) by
Lm1;
set eps = (
min (c,(b
/ (4
* z))));
A14:
0
< eps by
A10,
A11,
A12,
XXREAL_0: 15;
then
A15: z
< (z
+ eps) by
XREAL_1: 29;
(eps
* (2
* z))
<= ((b
/ (2
* (2
* z)))
* (2
* z)) by
A10,
XREAL_1: 64,
XXREAL_0: 17;
then (eps
* (2
* z))
<= (((b
/ 2)
/ (2
* z))
* (2
* z)) by
XCMPLX_1: 78;
then
A16: ((2
* z)
* eps)
<= (b
/ 2) by
A10,
XCMPLX_1: 87;
(eps
^2 )
<= (c
^2 ) by
A14,
Th15,
XXREAL_0: 17;
then (eps
^2 )
<= (b
/ 2) by
A13,
XXREAL_0: 2;
then
A17: (((2
* z)
* eps)
+ (eps
^2 ))
<= ((b
/ 2)
+ (b
/ 2)) by
A16,
XREAL_1: 7;
A18: ((z
+ eps)
^2 )
= ((z
^2 )
+ (((2
* z)
* eps)
+ (eps
^2 )));
a
= ((z
^2 )
+ b);
then ((z
+ eps)
^2 )
<= a by
A18,
A17,
XREAL_1: 6;
hence contradiction by
A1,
A7,
A2,
A6,
A15;
end;
suppose
A19: a
< (z
^2 ) & not z
<=
0 ;
set b = ((z
^2 )
- a);
set eps = (
min ((b
/ (2
* z)),z));
A20: ((z
- eps)
^2 )
= ((z
^2 )
- (((2
* z)
* eps)
- (eps
^2 )));
0
< b by
A19,
XREAL_1: 50;
then
0
< eps by
A19,
XXREAL_0: 15;
then
A21: (z
- eps)
< z by
XREAL_1: 44;
0
<= (eps
^2 ) by
XREAL_1: 63;
then
A22: (((2
* z)
* eps)
- (eps
^2 ))
<= (((2
* z)
* eps)
-
0 ) by
XREAL_1: 13;
(eps
* (2
* z))
<= ((b
/ (2
* z))
* (2
* z)) by
A19,
XREAL_1: 64,
XXREAL_0: 17;
then ((2
* z)
* eps)
<= b by
A19,
XCMPLX_1: 87;
then
A23: (((2
* z)
* eps)
- (eps
^2 ))
<= b by
A22,
XXREAL_0: 2;
A24:
0
<= (z
- eps) by
XREAL_1: 48,
XXREAL_0: 17;
a
= ((z
^2 )
- b);
then a
<= ((z
- eps)
^2 ) by
A20,
A23,
XREAL_1: 13;
hence contradiction by
A6,
A24,
A21;
end;
end;
hence contradiction;
end;
uniqueness by
Lm2;
end
theorem ::
SQUARE_1:17
Th17: (
sqrt
0 )
=
0
proof
(
sqrt (
0
^2 ))
=
0 by
Def2;
hence thesis;
end;
theorem ::
SQUARE_1:18
Th18: (
sqrt 1)
= 1
proof
(
sqrt (1
^2 ))
= 1 by
Def2;
hence thesis;
end;
Lm3:
0
<= x & x
< y implies (
sqrt x)
< (
sqrt y)
proof
assume that
A1:
0
<= x and
A2: x
< y;
A3: ((
sqrt y)
^2 )
= y by
A1,
A2,
Def2;
A4: ((
sqrt x)
^2 )
= x by
A1,
Def2;
0
<= (
sqrt y) by
A1,
A2,
Def2;
hence thesis by
A2,
A4,
A3,
Th15;
end;
theorem ::
SQUARE_1:19
1
< (
sqrt 2) by
Lm3,
Th18;
Lm4: (2
^2 )
= (2
* 2);
theorem ::
SQUARE_1:20
Th20: (
sqrt 4)
= 2 by
Def2,
Lm4;
theorem ::
SQUARE_1:21
(
sqrt 2)
< 2 by
Lm3,
Th20;
theorem ::
SQUARE_1:22
0
<= a implies (
sqrt (a
^2 ))
= a by
Def2;
theorem ::
SQUARE_1:23
a
<=
0 implies (
sqrt (a
^2 ))
= (
- a)
proof
A1: (a
^2 )
= ((
- a)
^2 );
assume a
<=
0 ;
hence thesis by
A1,
Def2;
end;
theorem ::
SQUARE_1:24
Th24:
0
<= a & (
sqrt a)
=
0 implies a
=
0
proof
0
<= a & (
sqrt a)
=
0 implies a
= (
0
^2 ) by
Def2;
hence thesis;
end;
theorem ::
SQUARE_1:25
Th25:
0
< a implies
0
< (
sqrt a)
proof
assume
A1:
0
< a;
then (
sqrt a)
<> (
0
^2 ) by
Def2;
hence thesis by
A1,
Def2;
end;
theorem ::
SQUARE_1:26
Th26:
0
<= x & x
<= y implies (
sqrt x)
<= (
sqrt y)
proof
per cases ;
suppose x
= y;
hence thesis;
end;
suppose
A1: x
<> y;
assume
A2:
0
<= x;
assume x
<= y;
then x
< y by
A1,
XXREAL_0: 1;
hence thesis by
A2,
Lm3;
end;
end;
theorem ::
SQUARE_1:27
0
<= x & x
< y implies (
sqrt x)
< (
sqrt y) by
Lm3;
theorem ::
SQUARE_1:28
Th28:
0
<= x &
0
<= y & (
sqrt x)
= (
sqrt y) implies x
= y
proof
assume that
A1:
0
<= x and
A2:
0
<= y and
A3: (
sqrt x)
= (
sqrt y);
assume x
<> y;
then x
< y or y
< x by
XXREAL_0: 1;
hence contradiction by
A1,
A2,
A3,
Lm3;
end;
theorem ::
SQUARE_1:29
Th29:
0
<= a &
0
<= b implies (
sqrt (a
* b))
= ((
sqrt a)
* (
sqrt b))
proof
assume that
A1:
0
<= a and
A2:
0
<= b;
A3:
0
<= (
sqrt a) by
A1,
Def2;
A4:
0
<= (
sqrt b) by
A2,
Def2;
((
sqrt (a
* b))
^2 )
= (a
* b) by
A1,
A2,
Def2
.= (((
sqrt a)
^2 )
* b) by
A1,
Def2
.= (((
sqrt a)
^2 )
* ((
sqrt b)
^2 )) by
A2,
Def2
.= (((
sqrt a)
* (
sqrt b))
^2 );
hence (
sqrt (a
* b))
= (
sqrt (((
sqrt a)
* (
sqrt b))
^2 )) by
A1,
A2,
Def2
.= ((
sqrt a)
* (
sqrt b)) by
A3,
A4,
Def2;
end;
theorem ::
SQUARE_1:30
Th30:
0
<= a &
0
<= b implies (
sqrt (a
/ b))
= ((
sqrt a)
/ (
sqrt b))
proof
assume that
A1:
0
<= a and
A2:
0
<= b;
A3: ((
sqrt b)
^2 )
= b by
A2,
Def2;
((
sqrt a)
^2 )
= a by
A1,
Def2;
then
A4: (((
sqrt a)
/ (
sqrt b))
^2 )
= (a
/ b) by
A3,
XCMPLX_1: 76;
A5:
0
<= (
sqrt b) by
A2,
Def2;
0
<= (
sqrt a) by
A1,
Def2;
hence thesis by
A5,
A4,
Def2;
end;
theorem ::
SQUARE_1:31
for a,b be
Real st
0
<= a &
0
<= b holds (
sqrt (a
+ b))
=
0 iff a
=
0 & b
=
0 by
Th17,
Th24;
theorem ::
SQUARE_1:32
0
< a implies (
sqrt (1
/ a))
= (1
/ (
sqrt a)) by
Th18,
Th30;
theorem ::
SQUARE_1:33
0
< a implies ((
sqrt a)
/ a)
= (1
/ (
sqrt a))
proof
assume
A1:
0
< a;
then (
sqrt a)
<> (
0
^2 ) by
Def2;
hence ((
sqrt a)
/ a)
= (((
sqrt a)
^2 )
/ (a
* (
sqrt a))) by
XCMPLX_1: 91
.= ((1
* a)
/ ((
sqrt a)
* a)) by
A1,
Def2
.= (1
/ (
sqrt a)) by
A1,
XCMPLX_1: 91;
end;
theorem ::
SQUARE_1:34
0
< a implies (a
/ (
sqrt a))
= (
sqrt a)
proof
assume
A1:
0
< a;
then (
sqrt a)
<> (
0
^2 ) by
Def2;
hence (a
/ (
sqrt a))
= ((a
* (
sqrt a))
/ ((
sqrt a)
^2 )) by
XCMPLX_1: 91
.= (((
sqrt a)
* a)
/ (1
* a)) by
A1,
Def2
.= ((
sqrt a)
/ 1) by
A1,
XCMPLX_1: 91
.= (
sqrt a);
end;
theorem ::
SQUARE_1:35
0
<= a &
0
<= b implies (((
sqrt a)
- (
sqrt b))
* ((
sqrt a)
+ (
sqrt b)))
= (a
- b)
proof
assume that
A1:
0
<= a and
A2:
0
<= b;
thus (((
sqrt a)
- (
sqrt b))
* ((
sqrt a)
+ (
sqrt b)))
= (((
sqrt a)
^2 )
- ((
sqrt b)
^2 ))
.= (a
- ((
sqrt b)
^2 )) by
A1,
Def2
.= (a
- b) by
A2,
Def2;
end;
Lm5:
0
<= a &
0
<= b & a
<> b implies (((
sqrt a)
^2 )
- ((
sqrt b)
^2 ))
<>
0
proof
assume that
A1:
0
<= a and
A2:
0
<= b and
A3: a
<> b;
A4:
0
<= (
sqrt a) by
A1,
Def2;
A5:
0
<= (
sqrt b) by
A2,
Def2;
(
sqrt a)
<> (
sqrt b) by
A1,
A2,
A3,
Th28;
hence thesis by
A4,
A5,
Lm2;
end;
theorem ::
SQUARE_1:36
0
<= a &
0
<= b & a
<> b implies (1
/ ((
sqrt a)
+ (
sqrt b)))
= (((
sqrt a)
- (
sqrt b))
/ (a
- b))
proof
assume that
A1:
0
<= a and
A2:
0
<= b and
A3: a
<> b;
thus (1
/ ((
sqrt a)
+ (
sqrt b)))
= (((
sqrt a)
- (
sqrt b))
/ (((
sqrt a)
^2 )
- ((
sqrt b)
^2 ))) by
A1,
A2,
A3,
Lm5,
Th10
.= (((
sqrt a)
- (
sqrt b))
/ (a
- ((
sqrt b)
^2 ))) by
A1,
Def2
.= (((
sqrt a)
- (
sqrt b))
/ (a
- b)) by
A2,
Def2;
end;
theorem ::
SQUARE_1:37
0
<= b & b
< a implies (1
/ ((
sqrt a)
+ (
sqrt b)))
= (((
sqrt a)
- (
sqrt b))
/ (a
- b))
proof
assume that
A1:
0
<= b and
A2: b
< a;
thus (1
/ ((
sqrt a)
+ (
sqrt b)))
= (((
sqrt a)
- (
sqrt b))
/ (((
sqrt a)
^2 )
- ((
sqrt b)
^2 ))) by
A1,
A2,
Lm5,
Th10
.= (((
sqrt a)
- (
sqrt b))
/ (a
- ((
sqrt b)
^2 ))) by
A1,
A2,
Def2
.= (((
sqrt a)
- (
sqrt b))
/ (a
- b)) by
A1,
Def2;
end;
theorem ::
SQUARE_1:38
0
<= a &
0
<= b implies (1
/ ((
sqrt a)
- (
sqrt b)))
= (((
sqrt a)
+ (
sqrt b))
/ (a
- b))
proof
assume that
A1:
0
<= a and
A2:
0
<= b;
per cases ;
suppose a
<> b;
hence (1
/ ((
sqrt a)
- (
sqrt b)))
= (((
sqrt a)
+ (
sqrt b))
/ (((
sqrt a)
^2 )
- ((
sqrt b)
^2 ))) by
A1,
A2,
Lm5,
Th11
.= (((
sqrt a)
+ (
sqrt b))
/ (a
- ((
sqrt b)
^2 ))) by
A1,
Def2
.= (((
sqrt a)
+ (
sqrt b))
/ (a
- b)) by
A2,
Def2;
end;
suppose
A3: a
= b;
then (1
/ ((
sqrt a)
- (
sqrt b)))
=
0 ;
hence thesis by
A3;
end;
end;
theorem ::
SQUARE_1:39
0
<= b & b
< a implies (1
/ ((
sqrt a)
- (
sqrt b)))
= (((
sqrt a)
+ (
sqrt b))
/ (a
- b))
proof
assume that
A1:
0
<= b and
A2: b
< a;
thus (1
/ ((
sqrt a)
- (
sqrt b)))
= (((
sqrt a)
+ (
sqrt b))
/ (((
sqrt a)
^2 )
- ((
sqrt b)
^2 ))) by
A1,
A2,
Lm5,
Th11
.= (((
sqrt a)
+ (
sqrt b))
/ (a
- ((
sqrt b)
^2 ))) by
A1,
A2,
Def2
.= (((
sqrt a)
+ (
sqrt b))
/ (a
- b)) by
A1,
Def2;
end;
theorem ::
SQUARE_1:40
for x,y be
Complex st (x
^2 )
= (y
^2 ) holds x
= y or x
= (
- y)
proof
let x,y be
Complex;
assume (x
^2 )
= (y
^2 );
then ((x
- y)
* (x
+ y))
=
0 ;
then (x
- y)
=
0 or (x
+ y)
=
0 ;
hence thesis;
end;
theorem ::
SQUARE_1:41
for x be
Complex st (x
^2 )
= 1 holds x
= 1 or x
= (
- 1)
proof
let x be
Complex;
assume (x
^2 )
= 1;
then ((x
- 1)
* (x
+ 1))
=
0 ;
then (x
- 1)
=
0 or (x
+ 1)
=
0 ;
hence thesis;
end;
theorem ::
SQUARE_1:42
0
<= x & x
<= 1 implies (x
^2 )
<= x
proof
assume that
A1:
0
<= x and
A2: x
<= 1;
per cases by
A1;
suppose
0
= x;
hence thesis;
end;
suppose
A3:
0
< x;
per cases by
A2,
XXREAL_0: 1;
suppose x
= 1;
hence thesis;
end;
suppose x
< 1;
hence thesis by
A3,
Th13;
end;
end;
end;
theorem ::
SQUARE_1:43
((x
^2 )
- 1)
<=
0 implies (
- 1)
<= x & x
<= 1
proof
assume ((x
^2 )
- 1)
<=
0 ;
then ((x
- 1)
* (x
+ 1))
<=
0 ;
hence thesis by
XREAL_1: 93;
end;
begin
theorem ::
SQUARE_1:44
Th44: a
<=
0 & x
< a implies (x
^2 )
> (a
^2 )
proof
assume that
A1: a
<=
0 and
A2: x
< a;
(
- x)
> (
- a) by
A2,
XREAL_1: 24;
then ((
- x)
^2 )
> ((
- a)
^2 ) by
A1,
Th16;
hence thesis;
end;
theorem ::
SQUARE_1:45
(
- 1)
>= a implies (
- a)
<= (a
^2 )
proof
assume (
- 1)
>= a;
then (
- (
- 1))
<= (
- a) by
XREAL_1: 24;
then (
- a)
<= ((
- a)
^2 ) by
XREAL_1: 151;
hence thesis;
end;
theorem ::
SQUARE_1:46
(
- 1)
> a implies (
- a)
< (a
^2 )
proof
assume (
- 1)
> a;
then (
- (
- 1))
< (
- a) by
XREAL_1: 24;
then (
- a)
< ((
- a)
^2 ) by
Th14;
hence thesis;
end;
theorem ::
SQUARE_1:47
(b
^2 )
<= (a
^2 ) & a
>=
0 implies (
- a)
<= b & b
<= a
proof
assume that
A1: (b
^2 )
<= (a
^2 ) and
A2: a
>=
0 ;
now
assume
A3: (
- a)
> b or b
> a;
now
per cases by
A3;
case (
- a)
> b;
then (
- (
- a))
< (
- b) by
XREAL_1: 24;
then (a
^2 )
< ((
- b)
^2 ) by
A2,
Th16;
hence contradiction by
A1;
end;
case b
> a;
hence contradiction by
A1,
A2,
Th16;
end;
end;
hence contradiction;
end;
hence thesis;
end;
theorem ::
SQUARE_1:48
(b
^2 )
< (a
^2 ) & a
>=
0 implies (
- a)
< b & b
< a
proof
assume that
A1: (b
^2 )
< (a
^2 ) and
A2: a
>=
0 ;
now
assume
A3: (
- a)
>= b or b
>= a;
now
per cases by
A3;
case (
- a)
>= b;
then (
- (
- a))
<= (
- b) by
XREAL_1: 24;
then (a
^2 )
<= ((
- b)
^2 ) by
A2,
Th15;
hence contradiction by
A1;
end;
case b
>= a;
hence contradiction by
A1,
A2,
Th15;
end;
end;
hence contradiction;
end;
hence thesis;
end;
theorem ::
SQUARE_1:49
Th49: (
- a)
<= b & b
<= a implies (b
^2 )
<= (a
^2 )
proof
assume that
A1: (
- a)
<= b and
A2: b
<= a;
per cases ;
suppose b
>=
0 ;
hence thesis by
A2,
Th15;
end;
suppose
A3: b
<
0 ;
(
- (
- a))
>= (
- b) by
A1,
XREAL_1: 24;
then ((
- b)
^2 )
<= (a
^2 ) by
A3,
Th15;
hence thesis;
end;
end;
theorem ::
SQUARE_1:50
(
- a)
< b & b
< a implies (b
^2 )
< (a
^2 )
proof
assume that
A1: (
- a)
< b and
A2: b
< a;
per cases ;
suppose b
>=
0 ;
hence thesis by
A2,
Th16;
end;
suppose
A3: b
<
0 ;
(
- (
- a))
> (
- b) by
A1,
XREAL_1: 24;
then ((
- b)
^2 )
< (a
^2 ) by
A3,
Th16;
hence thesis;
end;
end;
theorem ::
SQUARE_1:51
(a
^2 )
<= 1 implies (
- 1)
<= a & a
<= 1
proof
assume (a
^2 )
<= 1;
then ((a
^2 )
- (1
^2 ))
<= ((1
^2 )
- (1
^2 )) by
XREAL_1: 9;
then ((a
- 1)
* (a
+ 1))
<=
0 ;
hence thesis by
XREAL_1: 93;
end;
theorem ::
SQUARE_1:52
(a
^2 )
< 1 implies (
- 1)
< a & a
< 1
proof
assume (a
^2 )
< 1;
then ((a
^2 )
- (1
^2 ))
< ((1
^2 )
- (1
^2 )) by
XREAL_1: 9;
then ((a
- 1)
* (a
+ 1))
<
0 ;
hence thesis by
XREAL_1: 94;
end;
theorem ::
SQUARE_1:53
Th53: (
- 1)
<= a & a
<= 1 & (
- 1)
<= b & b
<= 1 implies ((a
^2 )
* (b
^2 ))
<= 1
proof
assume that
A1: (
- 1)
<= a and
A2: a
<= 1 and
A3: (
- 1)
<= b and
A4: b
<= 1;
A5:
0
<= (b
^2 ) by
XREAL_1: 63;
(a
^2 )
<= (1
^2 ) by
A1,
A2,
Th49;
then
A6: ((a
^2 )
* (b
^2 ))
<= (1
* (b
^2 )) by
A5,
XREAL_1: 64;
(b
^2 )
<= (1
^2 ) by
A3,
A4,
Th49;
hence thesis by
A6,
XXREAL_0: 2;
end;
theorem ::
SQUARE_1:54
Th54: a
>=
0 & b
>=
0 implies (a
* (
sqrt b))
= (
sqrt ((a
^2 )
* b))
proof
assume that
A1: a
>=
0 and
A2: b
>=
0 ;
(
sqrt (a
^2 ))
= a by
A1,
Def2;
hence thesis by
A1,
A2,
Th29;
end;
Lm6: (
- 1)
<= a & a
<= 1 & (
- 1)
<= b & b
<= 1 implies ((1
+ (a
^2 ))
* (b
^2 ))
<= (1
+ (b
^2 ))
proof
assume that
A1: (
- 1)
<= a and
A2: a
<= 1 and
A3: (
- 1)
<= b and
A4: b
<= 1;
((a
^2 )
* (b
^2 ))
<= 1 by
A1,
A2,
A3,
A4,
Th53;
then ((1
* (b
^2 ))
+ ((a
^2 )
* (b
^2 )))
<= (1
+ (b
^2 )) by
XREAL_1: 7;
hence thesis;
end;
theorem ::
SQUARE_1:55
Th55: (
- 1)
<= a & a
<= 1 & (
- 1)
<= b & b
<= 1 implies ((
- b)
* (
sqrt (1
+ (a
^2 ))))
<= (
sqrt (1
+ (b
^2 ))) & (
- (
sqrt (1
+ (b
^2 ))))
<= (b
* (
sqrt (1
+ (a
^2 ))))
proof
assume that
A1: (
- 1)
<= a and
A2: a
<= 1 and
A3: (
- 1)
<= b and
A4: b
<= 1;
A5: (a
^2 )
>=
0 by
XREAL_1: 63;
then
A6: (1
+ (a
^2 ))
>= (1
+
0 ) by
XREAL_1: 7;
(b
^2 )
>=
0 by
XREAL_1: 63;
then
A7: (
sqrt (1
+ (b
^2 )))
>=
0 by
Def2;
A8: (
sqrt (1
+ (a
^2 )))
>=
0 by
A5,
Def2;
A9:
now
per cases ;
suppose b
>=
0 ;
hence ((
- b)
* (
sqrt (1
+ (a
^2 ))))
<= (
sqrt (1
+ (b
^2 ))) by
A8,
A7;
end;
suppose
A10: b
<
0 ;
A11: ((
- b)
^2 )
>=
0 by
XREAL_1: 63;
((
- b)
* (
sqrt (1
+ (a
^2 ))))
= (
sqrt (((
- b)
^2 )
* (1
+ (a
^2 )))) by
A5,
A10,
Th54;
hence ((
- b)
* (
sqrt (1
+ (a
^2 ))))
<= (
sqrt (1
+ (b
^2 ))) by
A1,
A2,
A3,
A4,
A6,
A11,
Lm6,
Th26;
end;
end;
then (
- ((
- b)
* (
sqrt (1
+ (a
^2 )))))
>= (
- (
sqrt (1
+ (b
^2 )))) by
XREAL_1: 24;
hence thesis by
A9;
end;
theorem ::
SQUARE_1:56
(
- 1)
<= a & a
<= 1 & (
- 1)
<= b & b
<= 1 implies (b
* (
sqrt (1
+ (a
^2 ))))
<= (
sqrt (1
+ (b
^2 )))
proof
assume that
A1: (
- 1)
<= a and
A2: a
<= 1 and
A3: (
- 1)
<= b and
A4: b
<= 1;
A5: (
- 1)
<= (
- b) by
A4,
XREAL_1: 24;
(
- (
- 1))
>= (
- b) by
A3,
XREAL_1: 24;
then ((
- (
- b))
* (
sqrt (1
+ (a
^2 ))))
<= (
sqrt (1
+ ((
- b)
^2 ))) by
A1,
A2,
A5,
Th55;
hence thesis;
end;
Lm7: b
<=
0 & a
<= b implies (a
* (
sqrt (1
+ (b
^2 ))))
<= (b
* (
sqrt (1
+ (a
^2 ))))
proof
assume that
A1: b
<=
0 and
A2: a
<= b;
A3: ((
- a)
* (
sqrt (1
+ (b
^2 ))))
= (
sqrt (((
- a)
^2 )
* (1
+ (b
^2 )))) by
A1,
A2,
Th54;
a
< b or a
= b by
A2,
XXREAL_0: 1;
then (b
^2 )
< (a
^2 ) or a
= b by
A1,
Th44;
then
A4: (((b
^2 )
* 1)
+ ((b
^2 )
* (a
^2 )))
<= (((a
^2 )
* 1)
+ ((a
^2 )
* (b
^2 ))) by
XREAL_1: 7;
A5: (b
^2 )
>=
0 by
XREAL_1: 63;
A6: (a
^2 )
>=
0 by
XREAL_1: 63;
then ((
- b)
* (
sqrt (1
+ (a
^2 ))))
= (
sqrt (((
- b)
^2 )
* (1
+ (a
^2 )))) by
A1,
Th54;
then (
- (a
* (
sqrt (1
+ (b
^2 )))))
>= (
- (b
* (
sqrt (1
+ (a
^2 ))))) by
A6,
A3,
A4,
A5,
Th26;
hence thesis by
XREAL_1: 24;
end;
Lm8: for a,b be
Real st a
<=
0 & a
<= b holds (a
* (
sqrt (1
+ (b
^2 ))))
<= (b
* (
sqrt (1
+ (a
^2 ))))
proof
let a,b be
Real;
assume that
A1: a
<=
0 and
A2: a
<= b;
now
per cases ;
case b
<=
0 ;
hence thesis by
A2,
Lm7;
end;
case
A3: b
>
0 ;
(b
^2 )
>=
0 by
XREAL_1: 63;
then (
sqrt (1
+ (b
^2 )))
>
0 by
Th25;
then
A4: (a
* (
sqrt (1
+ (b
^2 ))))
<=
0 by
A1;
(a
^2 )
>=
0 by
XREAL_1: 63;
then (
sqrt (1
+ (a
^2 )))
>
0 by
Th25;
hence thesis by
A3,
A4;
end;
end;
hence thesis;
end;
Lm9: for a,b be
Real st a
>=
0 & a
>= b holds (a
* (
sqrt (1
+ (b
^2 ))))
>= (b
* (
sqrt (1
+ (a
^2 ))))
proof
let a,b be
Real;
assume that
A1: a
>=
0 and
A2: a
>= b;
(
- a)
<= (
- b) by
A2,
XREAL_1: 24;
then ((
- a)
* (
sqrt (1
+ ((
- b)
^2 ))))
<= ((
- b)
* (
sqrt (1
+ ((
- a)
^2 )))) by
A1,
Lm8;
then (
- (a
* (
sqrt (1
+ (b
^2 )))))
<= (
- (b
* (
sqrt (1
+ (a
^2 )))));
hence thesis by
XREAL_1: 24;
end;
theorem ::
SQUARE_1:57
a
>= b implies (a
* (
sqrt (1
+ (b
^2 ))))
>= (b
* (
sqrt (1
+ (a
^2 ))))
proof
assume
A1: a
>= b;
per cases ;
suppose a
>=
0 ;
hence thesis by
A1,
Lm9;
end;
suppose a
<
0 ;
hence thesis by
A1,
Lm7;
end;
end;
theorem ::
SQUARE_1:58
a
>=
0 implies (
sqrt (a
+ (b
^2 )))
>= b
proof
assume
A1: a
>=
0 ;
per cases ;
suppose b
<
0 ;
hence thesis by
A1,
Def2;
end;
suppose
A2: b
>=
0 ;
A3: (b
^2 )
>=
0 by
XREAL_1: 63;
(a
+ (b
^2 ))
>= (
0
+ (b
^2 )) by
A1,
XREAL_1: 6;
then (
sqrt (a
+ (b
^2 )))
>= (
sqrt (b
^2 )) by
A3,
Th26;
hence (
sqrt (a
+ (b
^2 )))
>= b by
A2,
Def2;
end;
end;
theorem ::
SQUARE_1:59
0
<= a &
0
<= b implies (
sqrt (a
+ b))
<= ((
sqrt a)
+ (
sqrt b))
proof
assume that
A1:
0
<= a and
A2:
0
<= b;
A3:
0
<= (
sqrt a) by
A1,
Def2;
0
<= (
sqrt (a
* b)) by
A1,
A2,
Def2;
then
0
<= ((
sqrt a)
* (
sqrt b)) by
A1,
A2,
Th29;
then
0
<= (2
* ((
sqrt a)
* (
sqrt b)));
then (a
+
0 )
<= (a
+ ((2
* (
sqrt a))
* (
sqrt b))) by
XREAL_1: 6;
then
A4: (a
+ b)
<= ((a
+ ((2
* (
sqrt a))
* (
sqrt b)))
+ b) by
XREAL_1: 6;
A5:
0
<= (
sqrt b) by
A2,
Def2;
(
sqrt ((a
+ ((2
* (
sqrt a))
* (
sqrt b)))
+ b))
= (
sqrt ((((
sqrt a)
^2 )
+ ((2
* (
sqrt a))
* (
sqrt b)))
+ b)) by
A1,
Def2
.= (
sqrt ((((
sqrt a)
^2 )
+ ((2
* (
sqrt a))
* (
sqrt b)))
+ ((
sqrt b)
^2 ))) by
A2,
Def2
.= (
sqrt (((
sqrt a)
+ (
sqrt b))
^2 ))
.= ((
sqrt a)
+ (
sqrt b)) by
A3,
A5,
Def2;
hence thesis by
A1,
A2,
A4,
Th26;
end;